Distance-sensitivity of German exports: first evidence from firm-product level data. Issue 3 (6th February 2017) - Wagner, Joachim
ABSTRACT: This article uses a tailor-made new data set of 7 580 251 observations for German exports at the firm-product-destination level to estimate a gravity equation and to investigate the link between the amount of firms' exports and the distance to destination countries. It is shown that, in line with stylized facts based on aggregate data, the quantity of exports declines significantly with distance within a firm for a given product.